Economic development with special reference to East Africa (London : Macmillan, 1964)
This book examines economic development in East Africa prior to 1964 covering topics like: Growth models, land, labour, capital, entrepreneurship, foreign trade, fiscal policy, agricultural policy among others.
Includes index.
lje 20/09/2018
Loans
Keywords: Kenneth Berrill; Economic development; East Africa